PENGARUH LINGKUNGAN KERJA DAN STRESS KERJA TERHADAP KEPUASAN KERJA TENAGA KESEHATAN PADA RSU INDAH KAB. ROKAN HILIR - -, Nadila Sri Ramadani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2024)
This research was conducted with the aim of determining the direct influence of work environment variables and work stress on job satisfaction of health workers at RSU Indah Rokan Hilir Regency. This type of research is using quantitative research. The population in this study was all health workers totaling 76 people. This study uses health workers as the object of research. The sampling method uses a saturated sample, which is as many as 76 respondents. The analytical methods used in processing this research data are descriptive statistical analysis, research instrument tests, classical assumption tests, coefficients of determination and multiple linear regression analysis using a significance level of 0.05. The data management of this study used the help of SPSS 25 software. Based on the results of the research conducted, it shows that work environment (X1) variables have a positive and significant effect on job satisfaction (Y) of health workers at RSU Indah Rokan Hilir Regency, while work stress (X2) variables have a negative and significant effect on job satisfaction(Y) of health workers at RSU Indah Rokan Hilir Regency. Based on the results of the study that the variables of work environment (X1) and work stress (X2) simultaneously affect job satisfaction (Y). Keywords: Work Environment, Work Stress, and Job Satisfaction